Decoupling engineering of formamidinium–cesium perovskites for efficient photovoltaics. Issue 10 (5th July 2022) - Chen, Haoran; Wang, Yong; Fan, Yingping; Chen, Yuetian; Miao, Yanfeng; Qin, Zhixiao; Wang, Xingtao; Liu, Xiaomin; Zhu, Kaicheng; Gao, Feng; Zhao, Yixin
Abstract: Although pure formamidinium iodide perovskite (FAPbI3 ) possesses an optimal gap for photovoltaics, their poor phase stability limits the long-term operational stability of the devices. A promising approach to enhance their phase stability is to incorporate cesium into FAPbI3 . However, state-of-the-art formamidinium–cesium (FA–Cs) iodide perovskites demonstrate much worse efficiency compared with FAPbI3, limited by the different crystallization dynamics of formamidinium and cesium, which result in poor composition homogeneity and high trap densities. We develop a novel strategy of crystallization decoupling processes of formamidinium and cesium via a sequential cesium incorporation approach. As such, we obtain highly reproducible, highly efficient and stable solar cells based on FA1 – x Cs x PbI3 ( x  = 0.05–0.16) films with uniform composition distribution in the nanoscale and low defect densities. We also revealed a new stabilization mechanism for Cs doping to stabilize FAPbI3, i.e. the incorporation of Cs into FAPbI3 significantly reduces the electron–phonon coupling strength to suppress ionic migration, thereby improving the stability of FA–Cs-based devices. Abstract : Sequential Cs incorporation strategy is developed to decouple crystallization of FACs perovskite with reduced electron-phonon coupling, resulting in highly stable FACs tri-iodide perovskite photovoltaics with record efficiency.